System Approach to the Evaluation of the Traction Electric Motor Quality - Arhun, Shch.; Migal, V.; Hnatov, A.; Hnatova, H.; Ulyanets, O. (EAI Endorsed Transactions on Energy Web, 2020)
The electric motor (EM) is one of the main components of any system. The EM quality is set at the design and manufacturing stages, and its technical condition is maintained during operation. Therefore, the development of methods for the EM quality determining at its all life cycle stages is urgent. In the paper, for the first time, we proposed the system approach to traction EM quality estimation on the vibration parameter basis. This approach differs in that the study of EM vibration is carried out in 1/3 octave spectrum of frequencies from 50 Hz to 10 kHz (dB), which allows revealing all existing faults or "weak places" of EM. This method is universal for all types of EM. It is based on the results of the largescale experiments using the system analysis and the objectives tree method and allows combining individual problem solutions to improve the quality of design, manufacture, and operation of EM into a single integrated system of quality assessment.
Keywords: smart grid; resilient technologies; clean power technologies; energy; intelligent systems; online monitoring; diagnostics; protection; training systems; electric power industry; education technologies; industrial electrical equipment and robots